THE ROLE OF ORGANIZATIONAL CULTURE AND ORGANIZATIONAL CLIMATE IN IMPROVING THE PERFORMANCE OF THE STATE CIVIL APPARATUS - Eden Komarudin Soeardi (INFOKUM, 2022)
Work might be accomplished not only as an obligation but also because there has to be an increase in performance along with the development and demands of the circumstance. It is possible to generate improved performance with the assistance of a healthy organizational culture and a positive organizational climate. The purpose of this research is to determine the extent to which organizational culture and climate have an impact on the efficiency of the State Civil Apparatus (ASN) in the context of their work in the social service sector of Subang Regency. A survey was conducted utilizing a questionnaire that was handed out to public officials working in the environment of the Subang district office. This allowed for the collection of data. The responses of all fifty people who filled out the questionnaire were analyzed using a quantitative method that included multiple regression analysis techniques. This was done in order to determine the impact that organizational culture and organizational climate variables had on ASN performance. According to the findings of the research, ASN performance at the workplace is significantly impacted by both the company culture and climate. Implications and suggestions for management are also covered in this section.